Nonlinear dynamic analysis for multi-storey RC structures with hybrid base isolation systems in presence of bi-directional ground motions - Cancellara, Donato; De Angelis, Fabio (Composite structures, 2016)
Multi-storey reinforced concrete (RC) structures may experience a weak structural behavior when subject to seismic and dynamic actions. In such cases the base isolation techniques are innovative strategies to protect the structures from seismic and dynamic loadings. In the present work three different hybrid base isolation systems are analyzed in order to protect reinforced concrete structures with regards to bi-directional ground motions. The three considered hybrid base isolation systems are the Elastomeric Spring Dampers operated in parallel with Friction Sliders, the Lead Rubber Bearings operated in parallel with Friction Sliders and the High Damping Rubber Bearings also operated in parallel with Friction Sliders. The analyzed base isolation systems have been designed in compliance to the European seismic codes EC2 and EC8. The base isolation devices are realized by elastomeric materials and steel-teflon bearings. The highly nonlinear behavior of the composite sliding isolation systems is investigated. A detailed analysis is reported of the hysteretic cycles of the friction slider bearings and the hysteretic cycles of the composite rubber bearing isolators. Bi-directional ground motions corresponding to recorded accelerograms have been considered as seismic actions. A spectrum compatibility analysis has been performed for the chosen recorded sets of accelerograms. A comparative analysis is illustrated for the three base isolated composite structures by reporting the time history of the base acceleration, the time history of the base shear, the time history of the base displacements and of the inter-storey drifts and the peak values of the base shear. The seismic and dynamic response of the considered base isolated structure is illustrated and a comparative analysis is finally presented between the base isolated structure with the three considered base isolation systems and the fixed base structure.